An Econometric Analysis of U.K. Money Demand in Monetary Trends in the United States and the United Kingdom by Milton Friedman and Anna J. Schwartz - Hendry, David F.; Ericsson, Neil R. (American Economic Review, 1991)
This paper evaluates an empirical model of U.K. money demand developed by Milton Friedman and Anna J. Schwartz in Monetary Trends in the United States and the United Kingdom. Testing reveals misspecification and hence the potential for an improved model. Using recursive procedures on their annual data, we obtain a better-fitting, constant, dynamic error-correction (cointegration) model. Results on exogeneity and encompassing imply that our money demand model is interpretable as a model of money but not of prices, since its constancy holds only conditionally on contemporaneous prices.